2020
DOI: 10.3390/ijerph17031120
|View full text |Cite
|
Sign up to set email alerts
|

Positional Obstructive Sleep Apnea Syndrome in Elderly Patients

Abstract: Background The purpose of this study was to evaluate the prevalence of position-dependent obstructive sleep apnea (POSA) in elderly patients (≥65 years old). Adult (range 19-65 years old) and elderly patients were also compared in order to show differences in the incidence of POSA between these two groups of patients. Methods A prospective bi-center study was performed between January 2018 and May 2019. A total of 434 participants underwent polysomnography (PSG) study at home (Embletta MPR). Body position duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Hence, we believe our study may be of value in understanding the demographic, clinical and PSG profile of POSA in this population. In this study, POSA was noted in 61%, in line with previous reports [11][12][13][14] and was predominantly noted among males (62%) and in non-Indigenous Australians (92%). This translates to three in every five patients with OSA have POSA and thus may merit greater focus and interventions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, we believe our study may be of value in understanding the demographic, clinical and PSG profile of POSA in this population. In this study, POSA was noted in 61%, in line with previous reports [11][12][13][14] and was predominantly noted among males (62%) and in non-Indigenous Australians (92%). This translates to three in every five patients with OSA have POSA and thus may merit greater focus and interventions.…”
Section: Discussionsupporting
confidence: 92%
“…There exists evidence in the literature for differences in POSA prevalence among differing ethnicities, most notably a potential increased prevalence among patients of Asian ethnicity compared to Caucasian, which may be related to differences in the craniofacial structure. [11][12][13][14][15][16]29 Further evidence from direct correlation studies however is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it varied from 21% to 49.3% according to the classification method but showed similar results to ours. 10) Based on the results of this study, the group without posture dependence showed no significant difference in the 'good compliance group' ratio compared to the position-dependent group, but the average CPAP usage time was significantly longer. There is a result of a previous study that stated that if patients who use CPAP devices change their position during sleep or their oxygen saturation decreased, they usually took off their CPAP devices.…”
Section: Discussionmentioning
confidence: 67%
“…When AHI differed by more than 50% between REM sleep and NREM sleep, we defined REM-related OSA. 10) Automatic positive airway pressure (APAP) devices were adjusted between a range of 4 to 13 cm H2O according to individual patient conditions. All patients using fixed CPAP underwent an all-night titration test or split-night PSG under the supervision of an experienced expert for determining optimal pressure according to the AASM guidelines.…”
Section: Methodsmentioning
confidence: 99%